Walking as a wandering ethic of (re)location: A public ‘pedagogy of hope’ - Blades , Genevieve (Journal of Public Pedagogies, 2020)
This paper considers the public pedagogy of location in relation to walking. I walk and write with and from my compass orientated to the Freirean notion of a ‘pedagogy of hope’. Using an autoethnographic account of a local walk, walking is (re)presented and interpreted as a wandering ethic of (re)location. Temporal and spatial dimensions of my walking are revealed in the social, cultural and ecological context of the bushfires and the pandemic. Drawing from scholars who theorize embodiment and the multiple natures of body~time~space, the inter and intra-actions with/in ecologies are presenced in a sensory narrative. To consider walking as a wandering ethic of (re)location, it is argued that various temporal, spatial, material, historical and cultural dimensions are contingent within the context of change as evident in the aftermath of bushfires and the pandemic. What I examine is the inter-play in relation to what is present and otherwise absent whilst walking that is interpreted as a ‘pedagogy of hope’ amidst the struggles and uncertainties of these times.